Community influences on trust in Swedish healthcare - Anna Mankell (Wellbeing, Space and Society)
A lack of trust in healthcare, often stemming from alienation or suspicion toward public institutions, may result in citizens forgoing essential support and treatments to which they are entitled and avoiding participation in preventive measures that benefit society as a whole. While the links between community characteristics and health are well established, this study aims to explore the influence of communities on trust in healthcare. Although trust in healthcare is generally high among the Swedish population, increasing diversity and segregation among neighborhoods make it relevant to examine variations in trust across local communities. Utilizing social capital theory, this study combines survey data from over 13,000 respondents with register data, linking individual data to local community characteristics through multi-level regression analyses. The findings reveal that individuals’ perceptions of their community have a stronger association with healthcare trust than the objective characteristics measured in the study, with community pessimism emerging as a significant factor, particularly for residents with a migrant background. Furthermore, it underscores the importance of understanding and distinguishing between community-level determinants of trust and how they differ between groups. Ultimately, this research will help identify neighborhoods with low healthcare trust and highlight the characteristics that correlate with diminishing trust, guiding targeted interventions.